Six-Bucket Sim-Savonius Hybrid Turbine: Experimental Analysis and Performance Evaluation - Khafaji, Salwan O. W.; Fath Ali, Ekhlas Q. A.; Al Khafaji, Dhirgham (Journal of Petroleum Research and Studies, 2025)
The growing awareness and apprehension regarding environmental issues have led to a surge in the demand for energy alternatives that are environmentally sustainable. Wind energy is widely recognized as a prominent and environmentally sustainable sort of electricity generation on a global scale. Fossil fuel is widely recognized as a crucial energy source, the accessibility of which is progressively declining. Nevertheless, wind power is considered a sustainable and renewable energy source that can serve as an alternative or supplementary option to conventional fossil fuels. Vertical axis wind turbines are good option for deployment in urban environments because to their exceptional characteristics, aesthetic appeal, minimal noise emissions, and enhanced safety measures. In order to accomplish these aims, a series of vertical axis wind turbines featuring many blades, constructed from light material, have been developed, produced, and subjected to experimental analysis to assess their performance. The turbine blade is created in the shape of a half-cylinder blade. The SIM-Savonius hybrid wind turbine's experimental evaluation involves manipulating blade angles and locations. This study investigates performance of the turbine at various speeds of winds and radius dimensions for the traditional turbine and (40cm, 50cm, 55cm) for the hybrid turbine. A graphical link was constructed between the power coefficient, blade angles, and tip speed ratio. Speed of wind, blade placement, blade count, and blade angle are all proven to have a major impact on wind turbine performance. The hybrid turbine has the highest power coefficient (31.111%) when the speed of the wind is 1.5 m/s, R is 50 cm, and r is 30 cm, the tip speed ratio (TSR) is 2.8, the blade angle is 45o. It should also be noted that the power factor of the multi-blade hybrid turbine increases by 1.383% when compared to the vertical axis wind turbine with six blades.